1991
DOI: 10.3109/02713689109020353
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpes simplex virus DNA sequences in corneal transplant recipients by polymerase chain reaction assays

Abstract: Polymerase chain reaction (PCR) assays were used to amplify herpes simplex virus type 1 (HSV-1) thymidine kinase (TK) sequences in DNA extracted from formalin-fixed, paraffin embedded corneas of patients undergoing corneal transplantation. PCR reamplification with an internal (nested) set of primers was required for detection in 10 of the 12 positive corneas indicating very low abundance of viral sequences. Three of the positive corneal samples were from failed corneal grafts. Overall, TK sequences were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…In different studies this rate was documented as 36% (Cantin et al 1991), and 22% (Kaye et al 2000). In our study we also demonstrated that six out of twenty eight (21%) corneal transplant patient without clinically obvious herpetic keratitis were carrying latent HSV virus in their corneas.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In different studies this rate was documented as 36% (Cantin et al 1991), and 22% (Kaye et al 2000). In our study we also demonstrated that six out of twenty eight (21%) corneal transplant patient without clinically obvious herpetic keratitis were carrying latent HSV virus in their corneas.…”
Section: Discussionsupporting
confidence: 72%
“…HSV virus can also undergo latency and reactivation in the cornea as an extraneuronal site after HSK disease (Pavan-Langston et al 1989;Rong et al 1991). In previous studies HSV detection rate by PCR ranged from 32% to 82% in donor cornea buttons of subjects with a past history of herpes keratitis (Cantin et al 1991;van Gelderen et al 2000;Kaye et al 2000).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vários métodos incluindo a cultura viral (14)(15)(16)(17)(18)(19) , reação da cadeia da polimerase (19)(20)(21)(22)(23)(24)(25) , imuno-histoquímica (25)(26) , e hibridização in situ (23) têm sido usados para o diagnóstico do HSV tipo 1 em córneas humanas. O trabalho de El-Aal AM (3) mostrou que a cultura do vírus herpes simples foi positiva em 10 (20,8%) de 48 casos suspeitos de ceratite herpética epitelial dendrítica com infiltrado subendotelial.…”
Section: Discussionunclassified
“…Furthermore, It seems that the prevalence of this virus in the general population of Iran is less than 1% [11], which is lower than the reports of the neighboring countries [12]. For this reason, the current study was designed to report the epidemiologic features of HBV and HCV in Iranian peoples with positive hepatitis screening test [13][14][15][16]. Iran is located in the Middle-East in a position like a bridge between Indian subcontinent, Arab peninsula, Middle Asia, and Europe.…”
mentioning
confidence: 99%